2013
DOI: 10.1097/jnr.0b013e3182a0af12
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Antiswelling and Analgesic Effects of Three Different Ice Pack Therapy Durations

Abstract: Research results found that the three different ice pack therapy durations could lower skin temperature and reduce partial pain. The different ice pack therapy durations would cause similar discomfort incidence rates in the three groups. Ice pack therapy for 10 minutes could reduce partial swelling and pain effectively. Accordingly, we suggest that 10 minutes is the optimal ice pack therapy duration for persons with soft tissue injuries. However, the ice pack therapy duration should be adjusted according to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Kullenberg et al's [ 17 ] study showed water ice packs were more effective than epidural analgesia in reducing pain degree after TKA. Kuo et al [ 18 ] also confirmed the effect of an ice pack on antiswelling and analgesic. Analysis from Thacoor and Sandiford [ 19 ] showed that cryotherapy had certain efficacy in reducing swelling and pain degrees after TKA.…”
Section: Discussionmentioning
confidence: 88%
“…Kullenberg et al's [ 17 ] study showed water ice packs were more effective than epidural analgesia in reducing pain degree after TKA. Kuo et al [ 18 ] also confirmed the effect of an ice pack on antiswelling and analgesic. Analysis from Thacoor and Sandiford [ 19 ] showed that cryotherapy had certain efficacy in reducing swelling and pain degrees after TKA.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, in our study, periorbital skin temperature decreased by 9.20 ºC after cold application. Also, another study showed that the average limb temperature of patients with soft tissue injury decreased by 9.77 °C after ice pack therapy for 20 minutes 16 .…”
Section: Change Of Skin Temperature After Cold Applicationmentioning
confidence: 98%
“…Cold application reduces blood leakage by causing vasoconstriction, slows down the metabolism of the damaged area and surrounding tissues, and reduces the inflammatory response in the damaged tissue 15,16 . These physiological effects of cold application are utilized to prevent and reduce swelling, edema and ecchymosis associated with soft tissue trauma 7,16 .…”
Section: Effect Of Cold Applicationmentioning
confidence: 99%
“…Some authors have reported limited benefit of cryotherapy on alleviating pain 14 or reducing blood loss 15 and inconsistent findings on decreasing swelling and improving mobility 16 post-TKA. The following discussion addresses these issues.…”
Section: Physiology Of Actionmentioning
confidence: 99%